Application of forward osmosis on dewatering of high nutrient sludge - Nguyen, Nguyen Cong; Chen, Shiao-Shing; Yang, Hung-Yin; Hau, Nguyen Thi (Bioresource technology, 2013)
[Display omitted] ► High nutrient sludge dewatering by forward osmosis was systematically investigated. ► Higher biomass loading achieved higher nutrient removal but more flux water decline. ► Membrane pore radius and sludge barrier layer played main role to remove nutrient. ► Membrane fouling was subject to cake formation and concentration polarization. ► Two FO stages are designed to incorporate with conventional biological treatment. A novel approach was designed to simultaneously apply low energy sludge dewatering and nutrient removal for activated sludge using forward osmosis (FO). In this study, the municipal wastewater sludge was spiked with different nutrient concentrations to evaluate FO dewatering performance. The results showed that sludge concentration reached 21,511 and 28,500mg/L after 28h from initial sludge concentration of 3000 and 8000mg/L with flow rate of 150mL/min. Moreover, nutrient and organic compounds in sludge solution were also successfully removed (around 96% of NH4+-N, 98% of PO43--P and 99% of dissolved organic carbon (DOC)) due to steric effect of FO membrane and multi barrier layer of sludge forming on membrane surface. Furthermore, the analysis from Scanning Electron Microscopy & Energy Dispersive X-ray Spectroscopy (SEM–EDS) images recorded that FO membrane was fouled by cake layer of sludge in the active layer and NaCl in the support layer.